2009
DOI: 10.1210/en.2008-1195
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to Structurally Diverse Antiestrogens Differ under Premenopausal and Postmenopausal Conditions: Evidence from in Vitro Breast Cancer Cell Models

Abstract: This study questioned whether the mechanisms of resistance to antiestrogens differ when acquired under premenopausal (Pre-M) vs. postmenopausal (PM) conditions and whether structurally diverse antiestrogens induce adaptation of differing signaling pathways. To address this issue, we conducted systematic studies under Pre-M vs. PM culture conditions with long-term exposure to different antiestrogens and examined the resultant "specific biologic signatures" of the various resistant cells. Estradiol stimulated gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 38 publications
(50 reference statements)
1
33
1
Order By: Relevance
“…Although BC is a hormone-dependent tumor, the present study found that menopause exhibited no significant effect on endocrine therapy resistance. This conclusion was inconsistent with some previous studies (26). A small sample size, selection criteria and different age-division ranges may also contribute to this conclusion.…”
Section: A B C D Econtrasting
confidence: 90%
“…Although BC is a hormone-dependent tumor, the present study found that menopause exhibited no significant effect on endocrine therapy resistance. This conclusion was inconsistent with some previous studies (26). A small sample size, selection criteria and different age-division ranges may also contribute to this conclusion.…”
Section: A B C D Econtrasting
confidence: 90%
“…Regardless of the 17b-estradiol (E2) concentration used (10 pmol/L or 1 nmol/L representative of a postmenopausal and premenopausal setting, respectively; ref. 36), elacestrant was able to decrease PGR to a basal level similar to control cells grown in the absence of E2 ( Fig. 1B; Supplementary Fig.…”
Section: T47dsupporting
confidence: 53%
“…It demonstrated that the presence of estrogen is necessary for GPR30 up-regulation/ translocation and might be an important milestone in development of acquired resistance. The importance of estrogen milieu for this process has been very recently confirmed [22]. GPR30 up-regulation can explain the increased sensibility of TAM-R cells to GPR30-specific agonist G1.…”
Section: Discussionmentioning
confidence: 84%